Lisinopril increases lung ACE2 levels and SARS-CoV-2 viral load and decreases inflammation but not disease severity in experimental COVID-19 - Silva-Santos, Yasmin; Pagni, Roberta Liberato; Gamon, Thais Helena Martins; de Azevedo, Marcela Santiago Pacheco; Bielavsky, Mônica; Darido, Maria Laura Goussain; de Oliveira, Danielle Bruna Leal; de Souza, Edmarcia Elisa; Wrenger, Carsten; Durigon, Edson Luiz; Luvizotto, Maria Cecília Rui; Ackerman, Hans Christian; et al. (Frontiers in Pharmacology, 2024)
COVID-19 causes more severe and frequently fatal disease in patients with pre-existing comorbidities such as hypertension and heart disease. SARS-CoV-2 virus enters host cells through the angiotensin-converting enzyme 2 (ACE2), which is fundamental in maintaining arterial pressure through the renin-angiotensin system (RAS). Hypertensive patients commonly use medications such as angiotensin-converting enzyme inhibitors (ACEi), which can modulate the expression of ACE2 and, therefore, potentially impact the susceptibility and severity of SARS-CoV-2 infection. Here we assessed whether treatment of ACE2-humanized (K18-hACE2) mice with the ACEi Lisinopril affects lung ACE2 levels and the outcome of experimental COVID-19. K18-hACE2 mice were treated for 21 days with Lisinopril 10 mg/kg and were then infected with 105 PFU of SARS-CoV-2 (Wuhan strain). Body weight, clinical score, respiratory function, survival, lung ACE2 levels, viral load, lung histology, and cytokine (IL-6, IL-33, and TNF-α) levels were assessed. Mice treated with Lisinopril for 21 days showed increased levels of ACE2 in the lungs. Infection with SARS-CoV-2 led to massive decrease in lung ACE2 levels at 3 days post-infection (dpi) in treated and untreated animals, but Lisinopril-treated mice showed a fast recovery (5dpi) of ACE2 levels. Higher ACE2 levels in Lisinopril-treated mice led to remarkably higher lung viral loads at 3 and 6/7dpi. Lisinopril-treated mice showed decreased levels of the pro-inflammatory cytokines IL-6 and TNF-α in the serum and lungs at 6/7dpi. Marginal improvements in body weight, clinical score and survival were observed in Lisinopril-treated mice. No differences between treated and untreated infected mice were observed in respiratory function and lung histology. Lisinopril treatment showed both deleterious (higher viral loads) and beneficial (anti-inflammatory and probably anti-constrictory and anti-coagulant) effects in experimental COVID-19. These effects seem to compensate each other, resulting in marginal beneficial effects in terms of outcome for Lisinopril-treated animals.